Computational Tradeoffs Under Bounded Resources - Horvitz, Eric; Zilberstein, Shlomo (Artificial Intelligence, 2001)
Over the nearly ﬁfty years of research in Artiﬁcial Intelligence, investigators have continued to highlight the computational hardness of implementing core competencies associated with intelligence. Key pillars of AI, including search, constraint propagation, belief updating, learning, decision making, and the associated real-world challenges of planning, perception, natural language understanding, speech recognition, and automated conversation continue to make salient the omnipresent wall of computational hardness.